2003
DOI: 10.1042/cs1040203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breathing air containing 3% carbon dioxide, 35% oxygen or a mixture of 3% carbon dioxide/35% oxygen on cerebral and peripheral oxygenation at 150 m and 3459 m

Abstract: The effects of gas mixtures comprising supplementary 3% carbon dioxide, 35% oxygen or a combination of 3% CO(2) plus 35% O(2) in ambient air have been compared on arterial blood gases, peripheral and cerebral oxygenation and middle cerebral artery velocity (MCAV) at 150 m and on acute exposure to 3459 m in 12 healthy subjects. Breathing 3% CO(2) or 35% O(2) increased arterial blood oxygen at both altitudes, and the CO(2)/O(2) combination resulted in the most marked rise. MCAV increased on ascent to 3459 m, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
5
18
0
Order By: Relevance
“…21 Breathing 7% CO 2 can increase CBF approximately 2-fold in both men 19 and women, 50 which is similar to what we observed in this study during exercise. CO 2 sensitivity is a measure of the level of ventilation for a given arterial CO 2 tension (PaCO 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…21 Breathing 7% CO 2 can increase CBF approximately 2-fold in both men 19 and women, 50 which is similar to what we observed in this study during exercise. CO 2 sensitivity is a measure of the level of ventilation for a given arterial CO 2 tension (PaCO 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Depressed PaCO 2 reduces CBF and increased PaCO 2 increases CBF. 19 For a given carbon dioxide production (VCO 2 ), the PaCO 2 is inversely proportional to the pulmonary ventilation (V E ): asV E increases PaCO 2 decreases and vice versa. Normally, as oxygen consumption (VO 2 ) andVCO 2 increase with exercise intensity, PaCO 2 increases until the onset of excess blood lactic acid accumulation, at which point there is a hyperventilation, that is, a respiratory compensation for the metabolic acidosis that reduces PaCO 2 and CBF.…”
mentioning
confidence: 99%
“…The study showed that the reduced air density at altitude has effects upon the pump, causing difficulty in entraining gas, and that high altitude has additional effects upon calibration of the instruments. There is ongoing interest in the effects of carbon dioxide (CO 2 ) on acclimatisation and mountain sickness at high altitude [1][2][3]. Experiments involving the measurement of CO 2 with capnography, however, have frequently been hampered by instrument malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing interest in the effects of carbon dioxide (CO 2 ) on acclimatisation and mountain sickness at high altitude [1][2][3]. Experiments involving the measurement of CO 2 with capnography, however, have frequently been hampered by instrument malfunction.…”
mentioning
confidence: 99%
“…Again, the available data are conflicting. In field studies, exposure to high altitude led to a significant increase in both CBF and MCAv [7,[10][11][12]. In an experimental study in a hypobaric chamber, however, an increase in MCAv could not be confirmed [9].…”
Section: Introductionmentioning
confidence: 97%